Evaluation of Groundwater Quality for the Construction Industry in Greater Noida (Jewar Region): Impact of Calcium Chloride Admixture on Groundwater Quality and Compressive Strength in the Construction Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In recent years, the increasing threat to groundwater quality due to human activities has become a matter of great concern. A vast majority of groundwater quality problems present today are caused by contamination and by overexploitation, or by combination of both. The parameters to be examined are pH, Chloride (as Cl), Organic Solid, Inorganic Solid, Sulphate (as SO3), Total Suspended Solid, Neutralization Value 0.02 H2SO4, Neutralization Value 0.02 NaOH, Turbidity, Conductivity for the groundwater samples of different locations which are Raunija, Rabupura, Banvaripur, Chachura, Jahangirpur, Kalupura, Jewar Banger and Jewar Khader. We are also testing the mean compressive strength of water using CaCl2 and comparing the result. This Study investigates the effect of Calcium Chloride (CaCl2) as an admixture on the Compressive Strength of concrete produced. It improves the compressive strength by 26.